THE INFLUENCE OF INCOME LEVEL, FAMILY EDUCATION, FINANCIAL LITERATURE ON RETIREMENT PLANNING MEDIATED BY SAVING BEHAVIOR - Ratna Catur Widyaningtya; Suhartono Suhartono (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
The pension program has 3 functions, namely the insurance function, the savings function and the pension function. The pension program has an insurance function because it can help provide guarantees to participants in overcoming the risk of losing income when they are in retirement age and or caused by death. The pension program has a savings function, because when you are in the program you are required to pay contributions. The pension program has a pension function, because it can provide benefits that will be received by participants when they retire which can be received periodically throughout life and so on. Taking into account these conditions, this study aims to analyze how much influence the level of income, family education, financial literacy is mediated by saving behavior on retirement planning. This study uses a quantitative method, namely by using a questionnaire, which contributes to this research as many as 195 respondents from private employees of Bank BPR UMKM Jawa Timur. This research uses SPSS analysis tool to measure Validity and Reliability and PLS-SEM. The results of this study reveal that income levels affect retirement planning, family education affects retirement planning, saving behavior affects retirement planning, financial literacy affects retirement planning. Family education and financial literacy affect retirement planning mediated by saving behavior